2000
DOI: 10.1177/107110070002100103
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Rupture Repair: Biomechanical Comparison of the Triple Bundle Technique versus the Krakow Locking Loop Technique

Abstract: This study was designed to compare the tensile strength of ruptured Achilles tendons repaired using either the triple bundle technique or the Krakow locking loop technique. Eight pairs of fresh frozen cadaveric Achilles tendons were harvested. A simulated "Achilles tendon rupture" was created 4 cm from the calcaneal insertion in all sixteen tendons by transversely cutting the tendon with a scalpel. One Achilles tendon "rupture" of a pair was repaired using the triple bundle technique, while the other tendon of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 10 publications
(2 reference statements)
9
86
2
3
Order By: Relevance
“…Triple bundle repair with early range of ankle motion, compared with nonoperative approach, have been reported by Beskin et al 18 to be successful, without any re-rupture after 3 years follow up, whereas a 7.7% re-rupture was noted in the conservative approach.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Triple bundle repair with early range of ankle motion, compared with nonoperative approach, have been reported by Beskin et al 18 to be successful, without any re-rupture after 3 years follow up, whereas a 7.7% re-rupture was noted in the conservative approach.…”
Section: Discussionmentioning
confidence: 87%
“…Early range of ankle motion and early weight bearing has frequently been recommended in several studies, 18,21,[23][24][25][26][27][28][29][30][31][32][33] and this is based on the advantage of a stronger tendon healing and faster functional recovery. To be able to apply these advantages on an old rupture of the tendon of Achilles, a strong and durable suturing technique would be required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bewährte Methoden sind End-zu-End-Nähte in den Techniken nach Bunnell, Kirchmeyr-Kessler oder Krackow [3,8,20,33,35]. Nach vergleichenden Untersuchungen von Jaakkola et al [38] sind die Nahttechniken von Krackow und die 3-Fach-Naht nach Bunnell am stabilsten.…”
Section: Offene Sehnennaht Der Achillessehnenrupturunclassified
“…When the knot is connected away from the rupture site, 2 different research studies have reported higher repair work strength. Jaakkola et al (32) discovered that the triple bundle is almost three-fold stronger in tension that the Krackow locking loop; this distinction is generally due to the increased number of strands crossing the rupture site. Another consider this difference is that the knot was tied far from the rupture site in the triple bundle method, whereas in the Krackow strategy, the knot is connected at the rupture site.…”
Section: Surgical Factors Influencing Tendon Tension Repair:-mentioning
confidence: 99%